World’s Top 2% Scientists List (career-long) 2022 - Agapiou, Athos (My University, 2026)
“World’s Top 2% Scientists List”, Included among the top 2% of highly cited scientists in the world, career-long (Ioannidis, John P.A., 2022, “September 2022 data-update for "Updated science-wide author databases of standardized citation indicators"”, Mendeley Data, V4, doi: 10.17632/btchxktzyw.4)
Keywords: Sciences